Emulsification Characteristics Using a Dynamic Woven Metal Microscreen Membrane - Rana Sabouni; Hassan G. Gomaa; Jiangshan Liu; Jesse Zhu (Membranes, 2016)
An oscillatory emulsification system for the production of oil in water emulsions using a commercially available low-cost woven metal microscreen (WMMS) is investigated. The system allows for independent control of both the oscillation frequencies and amplitudes such that it provides two degrees of freedom for controlling the emulsion properties. The investigations included the production of both surfactant and particle-stabilized emulsions. The average droplet size was found to decrease when both the oscillation frequency and amplitude was increased. For surfactant-stabilized emulsions, using bi-surfactants in both the continuous and dispersed phases resulted in a smaller droplet size due to lower interfacial tension. For particle-stabilized emulsions, both the hydrodynamics of the system and the hydrophobic and hydrophilic nature of the stabilizing particles influenced the interfacial properties at the oil–water interface, which in turn affected the final droplet size and distribution with potential droplet breakage. In absence of the latter, a simple torque balance model can be used to reasonably predict the average emulsion droplet size.